Islamic Banks’ Return on Depositors and Conventional Banks’ Deposit Interest: Is there Causality? Evidence of Causality from Bangladesh. - Abdus Samad; Mohammad Ashraful Ferdous Chowdhury (International Journal of Economics and Financial Issues, 2017)
The critiques of the Islamic bank allege that the depositors’ return and the return on loans of the Islamic bank is nothing but the interest rate of the conventional banks and they simply follow the conventional banks interest rate. This paper empirically investigates the causal relation and the causal direction between the conventional banks’ interest rate and the Islamic banks’ return applying VEC model. The results of the VER Granger Causality/Block Exogeneity Wald Tests show unidirectional causal relation and the direction of causality ran from the Islamic banks’ rate of return to the conventional banks’ interest rates. Keywords: Conventional Bank Interest rate, Islamic Bank deposit and loan rate, Granger causality, Bangladesh JEL Classifications: G21; F31